Etika Kuliah Daring Seminari Tinggi San Giovanni XXIII dalam Perspektif Etika Franz Magnis Suseno - Rici Rici; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
Online Ethics is the ethical norm for online lectures for students during the Covid-19 Pandemic. The online lecture process demands great freedom and responsibility from students. Online lecture ethics (Etika Online) presents moral attitudes and principles of moral virtue as an orientation for students to become good people. This study was conducted to determine the student ethos regarding freedom and responsibility when studying online. How students run online lectures during the Pandemic on the basis of standards of morality and the principles of virtue of morality. This research method uses a qualitative method which is carried out at the San Giovanni XXIII Seminary Malang by distributing questionnaires and conducting interviews via WhatsApp and Google Froms. Research sources are students in semester IV and VI. The study of literature as the main focus in this study explores primary data on ethical themes and reading critical reflections as secondary data, especially those that discuss ethical theory. The results of the research analysis showed that with online lectures, students felt free but also had a big responsibility to develop their creativity and potential. And the ethical implications of Franz Magnis Suseno about the basic attitudes of morality and the principles of virtue of morality to become students with etiquette in attending online lectures.